STUDY OF THE RELATIONSHIP BETWEEN GREEN BONDS, OTHER FINANCIAL ASSETS, AND SUSTAINABLE FINANCE: A SYSTEMATIC LITERATURE REVIEW - Muhammad Irawan Saputra; Duwi Rahayu (Antis Publisher, 2025)
Objective: This study aims to map and analyse the relationship between green bonds, sustainable finance, and other financial assets to understand thematic developments, empirical findings, and research gaps in the post-Paris Agreement era. Method: A systematic literature review was conducted using the SPAR-4-SLR protocol combined with bibliometric analysis through VOSviewer and Biblioshiny on 110 peer-reviewed articles published between 2018 and 2025. Results: The analysis reveals an exponential growth in publications with an annual rate of 55.12%, highlighting the rapid expansion of the sustainable finance research ecosystem. Empirical evidence consistently confirms the presence of a greenium—green bonds offering lower yields than conventional bonds—along with diversification benefits and reductions in portfolio volatility. Thematic mapping identifies six dominant clusters: sustainable finance, green finance, ESG/SDGs, renewable energy, portfolio and risk, and green innovation, while investor attention emerges as an under-studied moderating variable in cross-asset dynamics. Novelty: This study contributes by identifying the most influential works, structuring the intellectual landscape of sustainable finance, and proposing a future research agenda focused on deepening cross-asset connectivity and enhancing policy relevance, particularly in emerging markets such as Indonesia.